The Study of the Foaming Ability of Magnesium Laureth Sulfate at Different pH Values - Petrovskaya, L. S. (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: The aim of our work was to study the physicochemical properties of the surfactant to compare the foaming ability (foam number and foam stability) at different pH values as well as to conduct them icroscopic analysis of the massive foam of the samples with magnesium laureth sulfate. Materials and Methods: 70% magnesium laureth sulfate (â€œEÐžÐ¡â€, Belgium) was chosen as an anionic surfactant providing the safe cleansing of the skin and its appendages. The samples were given by the Pharmaceutical Science and Research Centre â€œAliyance Krasotyâ€ (Beauty Alliance, Kyiv, Ukraine). Lactic acid (lactic acid, â€œGalacticâ€, Belgium) was used as a pH adjuster of the foaming base value. The foaming ability of the test samples was determined by the method specified in DSTU ISO 696:2005 â€œDetermination of the foaming ability by the modified method of Ross-Milesâ€ and GOST 22567.1-77 â€œSynthetic detergentsâ€. For this, we used the method for determining the foaming ability. The level of the pH value of the test samples was determined by potentiometry (SPhU 1.2, 2.2.3) using a â€œÑ€Ð Meter Metrohm 744.â€ The quality of the bases prepared was assessed according to the following criteria: Appearance, organoleptic indicators (color, odor), determination of the Ñ€Ð value, the foaming ability (foam number, foam stability). These indicators were considered for the qualitative assessment of the current foaming detergents according to DSTU 4315:2004 â€œCosmetic products for cleansing the skin and hairâ€ and TU U 24.5-31640335-002:2007 â€œSkin care cleaning products.â€ According to DSTU 4315:2004, the foam number should not be <145.0 mm, and the foam stability should be 0.8-1.0 c.u. In addition, the microscopic analysis of the foam was conducted using a â€œKonus-Akademyâ€ laboratory microscope with the ScopeTek DCM510 eyepiece camera. Results and Discussion: When analyzing the data obtained for the foaming ability of the test sample of the anionic surfactant, it was found that it had a relatively high value of both the foam number and the foam stability, and it corresponded to the requirements of the current normative documents of Ukraine. The next step of our experiment was to determine the foaming ability of magnesium laureth sulfate at the acid Ñ€Ð value (3.5-4.0). This research stage was necessary for comparison of the physicochemical properties of the surfactant selected. This is due to the peculiarities of foaming detergent development. The Ñ€Ð was adjusted using lactic acid. According to the experimental data, it was found that at the acid Ñ€Ð range, the foaming base with magnesium laureth sulfate insignificantly improved its indicators of the foaming lability (both the foam number and the foam stability). Conclusions: It has been found that by the main physicochemical indicators (foaming ability) of quality, the foaming bases with magnesium laureth sulfate in two Ñ€Ð ranges fully comply with the standard values of the existing state standards of Ukraine. When studying the structure of the massive foam in the samples with magnesium laureth sulfate at the Ñ€Ð ranges of 5.5-6.0 and 3.5-4.0 using microscopy, it has been determined that in both cases, the foam has a stable structured system, i.e., it has a spherical shape and is characterized by the minimal surface energy, thus indicating its stability.